A scaled-up, CSP integrated, high-temperature volumetric receiver with a semi-transparent packed-bed absorber - Mohammadreza Sedighi; Mehdi Aghaei Meybodi; Robert A. Taylor; Ricardo Vasquez Padilla; Andrew C. Beath (Energy Conversion and Management: X, 2022)
Conventional solar thermal receivers are limited to operating at temperatures below 600 °C due to the operational limitations of liquid heat transfer fluids (HTFs). In addition, pushing to temperatures above 600 °C leads to a steep trade-off between the thermodynamic availability of the outlet fluid and receiver efficiency due to the fact that radiation losses are ∝T4. This paper investigates a nascent gas-phase receiver incorporating a semi-transparent packed bed absorber, which is capable of mitigating these issues. To date, this new class of receiver design has only been modelled on the small-scale under design-point direct normal irradiance. To obtain an understanding of the annual performance, the novel design was scaled up and integrated with a CSP system by linking MATLAB with SolarPilot to conduct a transient analysis using real-time solar irradiance data. The results demonstrated that the gas-phase receiver can feed a gas turbine with an annual temperature above 700 °C (i.e., a > 700 °C gas can be delivered to the turbine for ∼65 % of the annual operating hours). In terms of selecting a gaseous HTF, a previously unexplored area, helium was found to provide the best performance, with ∼1 % and ∼9.2 % increases in the annual power and outlet temperature, respectively, as compared to air. As another alternative, CO2 provided almost the same annual output as air. A non-dimensional analysis also revealed that excessive operating pressure would not lead to an actual gain in the overall receiver performance. The developed method also provided insight into the economic viability of the scaled-up receiver design. It was found that this design is most economic for small, modular designs. For example, a modular receiver design with a single tower integrated with a 9 MWe turbine outperformed the conventional system (i.e., a Rankine cycle operating at 574 °C) with a ∼38 % decrease in the LCOE. Overall, this research provides the first theoretical integration of a semi-transparent packed-bed receiver design within a high-temperature, small-scale CSP system.